Evaluation of transthoracic and transesophageal echocardiographic findings in acute ischemic stroke - (:unkn) unknown (My University, 2001)
Objective: Approximately 20% of all ischemic strokes are the result of an embolus originating from the heart. Transthoracic echocardiography (TTE) has long been used to evaluate the cardiac source of emboli but recently transesophageal echocardiography (TEE), which has higher yield for detecting left atrium, aortic arch and left atrial appendage lesions, is recommended for the assessment of patients with clinical risk factors for cardioembolism or unexplained stroke. Methods: In this study, the diagnostic yield of TTE and TEE for detecting potential cardiac sources of the embolus was compared in 46 consecutive patients (26 men and 20 women, aged 23-84 years) with transient ischemic attack (TIA) or acute ischemic stroke. Results: TTE revealed a potential cardiac source of embolism in 12 (26%) patients, all of whom had clinical evidence of heart disease, TEE detected potential cardiac sources of embolism in 32 (69%) patients; 7 (21%) of these had no clinical evidence of heart disease. Conclusion: TEE is a superior technique to TTE for identifying potential cardiac source of the embolus and should be recommended for early management and prevention of further stroke in patients with underlying heart disease or unexplained cerebrovascular accident.
Keywords: Cardiac source of embolism; Ischemic stroke; Transesophageal echocardiography; Transthoracic echocardiography